Ti-Al-TiC / Cu composite coating for improving current-carrying friction and wear performance of copper alloy and preparation method of Ti-Al-TiC / Cu composite coating

By using Ti, Al and TiC powders to prepare Ti-Al-TiC spherical powder and combining it with Cu powder, the Ti-Al-TiC/Cu composite coating is prepared by atmospheric plasma spraying technology, which solves the high cost of Ti2AlC spherical powder and the easy thermal spraying. The decomposition problem has achieved efficient and low-cost copper alloy current-carrying friction and wear performance improvement.

CN119287306APending Publication Date: 2025-01-10ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411091035.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The high cost of Ti2AlC spherical powder and the thermal spraying temperature are too high, which makes it easy to decompose during the spraying process and cannot fully exert its excellent performance, resulting in limited effectiveness of direct spraying of Ti2AlC coating.

Method used

Ti-Al-TiC spherical powder is prepared by spray granulation, and mechanically mixed with Cu powder. The Ti-Al-TiC/Cu composite coating with 200-300μm thick is prepared by atmospheric plasma spraying to reduce the Cost and control process parameters to avoid decomposition.

Benefits of technology

The Ti-Al-TiC/Cu composite coating was achieved at low cost, and combined with the TiAl alloy phase, the lubricated conductive phase Ti2AlC phase and the unreacted TiC reinforced phase, significantly improving the current-carrying friction and wear performance of copper alloys, with high hardness and Conductive properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287306A_ABST
    Figure CN119287306A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surface current-carrying friction and wear protection of copper alloy, in particular to a Ti-Al-TiC / Cu composite coating for improving current-carrying friction and wear performance of copper alloy and a preparation method thereof.The preparation method comprises the steps that firstly, raw materials including Ti powder, Al powder and TiC powder are selected, the Ti-Al-TiC powder is prepared in a spray granulation mode, and then the Ti-Al-TiC composite coating is prepared; and then the Cu powder is mixed through an automatic stirrer to prepare composite coating powder, wherein the content of Ti-Al-TiC powder accounts for 30%-50% of the molar ratio of the total powder. Atmospheric plasma spraying equipment is used for preparing the coating, spraying parameters are as follows: the current is 450-500 A, the power is 30-33 kw, the main gas flow of argon is 30-45 L / min, the linear speed is 450-550 mm / s, the spraying distance is 90-110 mm, and the Ti-Al-TiC / Cu composite coating with the thickness of 200-300 microns is prepared on the surface of a Cu matrix. And before spraying, carrying out surface sand blasting roughening and alcohol ultrasonic cleaning on the Cu substrate. The phase of the coating prepared under the condition comprises a conductive wear-resistant phase Ti2AlC formed by reaction, an alloy phase TiAl phase, unreacted TiC and other phases, and low-cost preparation of the current-carrying frictional wear resistant composite coating is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface current-carrying friction and wear protection for copper alloys, and in particular to a Ti-Al-TiC / Cu composite coating for improving current-carrying friction and wear performance of copper alloys and a preparation method thereof. Background Art

[0002] Copper alloy has high conductivity and low contact resistance, and is an excellent conductive material. At present, it is widely used in key technical fields such as pantograph slides and electromagnetic guide rails of high-speed railways. In this service environment, the material is required to have the performance of resisting current-carrying friction and wear, which requires the material to have high wear resistance and conductivity. Surface coating technology is often used to solve problems such as the poor wear resistance of copper alloy materials themselves. 2 As a MAX phase, AlC material has moderate hardness, friction reduction, wear resistance, and good conductivity, so it has a good application prospect in the direction of conductive wear-resistant coating materials. 2 AlC spherical powder has a high cost, and the high thermal spraying temperature makes it easy to decompose during the spraying process, which makes Ti 2 The excellent performance of AlC phase cannot be fully utilized, so directly spraying Ti 2 AlC coatings have had limited success.

[0003] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of Ti 2 AlC spherical powder has a high cost, and the high thermal spraying temperature makes it easy to decompose during the spraying process, which makes Ti 2 The excellent performance of AlC phase cannot be fully utilized, so directly spraying Ti 2 In order to solve the problem that AlC coating has limited effectiveness, a Ti-Al-TiC / Cu composite coating and a preparation method thereof are provided for improving the current-carrying friction and wear properties of copper alloy.

[0005] In order to achieve the above object, the present invention discloses a method for preparing a Ti-Al-TiC / Cu composite coating for improving the current-carrying friction and wear performance of a copper alloy, comprising the following steps:

[0006] S1, adding Ti powder, Al powder, TiC powder and polyvinyl alcohol into deionized water and stirring to prepare Ti-Al-TiC powder granulation slurry;

[0007] S2, preparing Ti-Al-TiC spherical powder by spray granulation of the Ti-Al-TiC powder obtained in step S1 into granulated slurry;

[0008] S3, mechanically mixing the Ti-Al-TiC spherical powder obtained in step S2 with Cu powder to obtain Ti-Al-TiC / Cu composite powder;

[0009] S4, sandblasting roughening and alcohol ultrasonic cleaning of the sprayed surface of the Cu substrate;

[0010] S5, using the Ti-Al-TiC / Cu composite powder obtained in step S3 to perform atmospheric plasma spraying on the Cu substrate to obtain a Ti-Al-TiC / Cu composite thick coating of 200 to 300 μm.

[0011] In the step S1, the molar ratio of Ti powder, Al powder and TiC powder is 1:1:1, and the particle size of Ti powder is 2-15 μm, the particle size of Al powder is 1-5 μm, and the particle size of TiC powder is 3-10 μm.

[0012] In the step S1, the mass of deionized water is 1.5 times the mass of the powder, and the mass of polyvinyl alcohol is 2.5% of the mass of the powder.

[0013] In the step S3, the Ti-Al-TiC composite powder accounts for 30-50% of the total molar ratio, and the Cu powder is a spherical powder of 30-60 μm.

[0014] In step S5, the spraying parameters are as follows: current is 450-500A, power is 30-33kw, main gas flow rate of argon is 30-45L / min, line speed is 450-550mm / s; spraying distance is 90-110mm.

[0015] The invention also discloses a Ti-Al-TiC / Cu composite coating which is prepared by the preparation method and is used to improve the current-carrying friction and wear performance of the copper alloy.

[0016] Compared with the prior art, the invention has the following beneficial effects: the invention selects low-cost Ti, Al and TiC powders, prepares Ti-Al-TiC spherical powder by granulation, and adopts atmospheric plasma spraying to prepare Ti-Al-TiC / Cu composite coating, the preparation method is simple, the preparation cost is low, and the TiAl alloy phase, the lubricating conductive phase Ti are obtained by process control. 2 The AlC phase and the unreacted TiC reinforcing phase are well bonded to the matrix, have high hardness and electrical conductivity, can resist current-carrying friction and wear, and realize the low-cost preparation of the current-carrying friction and wear resistant composite coating, which can be applied to the surface of copper alloy materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the cross-sectional morphology of the coating according to the embodiment of the present invention;

[0018] Figure 2The hardness test results of the embodiment of the present invention and comparative example 3 are shown;

[0019] Figure 3 The conductivity test results of the embodiment of the present invention and comparative example 4 are shown;

[0020] Figure 4 The porosity test results of the embodiment of the present invention and comparative example 5 are shown;

[0021] Figure 5 The hardness test results of the embodiment of the present invention and comparative example 6 are shown;

[0022] Figure 6 The current-carrying friction and wear weight loss test results of the embodiment of the present invention and the comparative example 1 when the current is 80A;

[0023] Figure 7 The test results of current-carrying friction and wear weight loss of the embodiment of the present invention and the comparative example 2 when the current is 80A. DETAILED DESCRIPTION

[0024] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0025] Example

[0026] S1: Ti powder, Al powder, TiC powder and polyvinyl alcohol are added into deionized water and stirred to prepare Ti-Al-TiC powder granulation slurry. The molar ratio of Ti powder, Al powder and TiC powder is 1:1:1, and the particle size of Ti powder is 2-15 μm, the particle size of Al powder is 1-5 μm, and the particle size of TiC powder is 3-10 μm.

[0027] S2: The Ti—Al—TiC powder granulation slurry obtained in step S1 is prepared into Ti—Al—TiC spherical powder by spray granulation.

[0028] S3: Mechanically mix the Ti-Al-TiC powder obtained in S2 with Cu powder, wherein the Ti-Al-TiC composite powder accounts for 40% of the total molar ratio, and the Cu powder is a 30-60 μm spherical powder, to obtain a Ti-Al-TiC / Cu composite powder.

[0029] S4: The sprayed surface of the Cu substrate is roughened by sandblasting and cleaned by alcohol ultrasonic cleaning.

[0030] S5: Atmospheric plasma spraying was performed with a current of 460A, a power of 30kw, a main gas flow rate of argon gas of 45L / min, a line speed of 500mm / s, and a spraying distance of 100mm to obtain a Ti-Al-TiC / Cu composite coating.

[0031] Comparative Example 1

[0032] Untreated copper alloy.

[0033] Comparative Example 2

[0034] S1: Ti powder, Al powder, TiC powder and polyvinyl alcohol are added into deionized water and stirred to prepare Ti-Al-TiC powder granulation slurry. The molar ratio of Ti powder, Al powder and TiC powder is 1:1:1, and the particle size of Ti powder is 5-30 μm, the particle size of Al powder is 5-15 μm, and the particle size of TiC powder is 5-25 μm.

[0035] S2: The Ti—Al—TiC powder granulation slurry obtained in step S1 is prepared into Ti—Al—TiC (coarse powder) spherical powder by spray granulation.

[0036] S3: Mechanically mix the Ti-Al-TiC (coarse powder) powder obtained in S2 with Cu powder, wherein the Ti-Al-TiC (coarse powder) composite powder accounts for 40% of the total molar ratio, and the Cu powder is a 30-60 μm spherical powder, to obtain Ti-Al-TiC (coarse powder) / Cu composite powder.

[0037] S4: The sprayed surface of the Cu substrate is roughened by sandblasting and cleaned by alcohol ultrasonic cleaning.

[0038] S5: Atmospheric plasma spraying was performed with a current of 460A, a power of 30kw, a main gas flow rate of argon gas of 45L / min, a line speed of 500mm / s, and a spraying distance of 100mm to obtain a Ti-Al-TiC / Cu composite coating.

[0039] Comparative Example 3

[0040] S1: Ti powder, Al powder, TiC powder and polyvinyl alcohol are added into deionized water and stirred to prepare Ti-Al-TiC powder granulation slurry. The molar ratio of Ti powder, Al powder and TiC powder is 1:1:1, and the particle size of Ti powder is 2-15 μm, the particle size of Al powder is 1-5 μm, and the particle size of TiC powder is 3-10 μm.

[0041] S2: The Ti—Al—TiC powder granulation slurry obtained in step S1 is prepared into Ti—Al—TiC spherical powder by spray granulation.

[0042] S3: Mechanically mix the Ti-Al-TiC powder obtained in S2 with Cu powder, wherein the Ti-Al-TiC composite powder accounts for 20% of the total molar ratio, and the Cu powder is a 30-60 μm spherical powder, to obtain a Ti-Al-TiC / Cu composite powder.

[0043] S4: The sprayed surface of the Cu substrate is roughened by sandblasting and cleaned by alcohol ultrasonic cleaning.

[0044] S5: Atmospheric plasma spraying was performed with a current of 460A, a power of 30kw, a main gas flow rate of argon gas of 45L / min, a line speed of 500mm / s, and a spraying distance of 100mm to obtain a Ti-Al-TiC / Cu composite coating.

[0045] Comparative Example 4

[0046] S1: Ti powder, Al powder, TiC powder and polyvinyl alcohol are added into deionized water and stirred to prepare Ti-Al-TiC powder granulation slurry. The molar ratio of Ti powder, Al powder and TiC powder is 1:1:1, and the particle size of Ti powder is 2-15 μm, the particle size of Al powder is 1-5 μm, and the particle size of TiC powder is 3-10 μm.

[0047] S2: The Ti—Al—TiC powder granulation slurry obtained in step S1 is prepared into Ti—Al—TiC spherical powder by spray granulation.

[0048] S3: Mechanically mix the Ti-Al-TiC powder obtained in S2 with Cu powder, wherein the Ti-Al-TiC composite powder accounts for 60% of the total molar ratio, and the Cu powder is a 30-60 μm spherical powder, to obtain a Ti-Al-TiC / Cu composite powder.

[0049] S4: The sprayed surface of the Cu substrate is roughened by sandblasting and cleaned by alcohol ultrasonic cleaning.

[0050] S5: Atmospheric plasma spraying was performed with a current of 460A, a power of 30kw, a main gas flow rate of argon gas of 45L / min, a line speed of 500mm / s, and a spraying distance of 100mm to obtain a Ti-Al-TiC / Cu composite coating.

[0051] Comparative Example 5

[0052] S1: Ti powder, Al powder, TiC powder and polyvinyl alcohol are added into deionized water and stirred to prepare Ti-Al-TiC powder granulation slurry. The molar ratio of Ti powder, Al powder and TiC powder is 1:1:1, and the particle size of Ti powder is 2-15 μm, the particle size of Al powder is 1-5 μm, and the particle size of TiC powder is 3-10 μm.

[0053] S2: The Ti—Al—TiC powder granulation slurry obtained in step S1 is prepared into Ti—Al—TiC spherical powder by spray granulation.

[0054] S3: Mechanically mix the Ti-Al-TiC powder obtained in S2 with Cu powder, wherein the Ti-Al-TiC composite powder accounts for 40% of the total molar ratio, and the Cu powder is a 30-60 μm spherical powder, to obtain a Ti-Al-TiC / Cu composite powder.

[0055] S4: The sprayed surface of the Cu substrate is roughened by sandblasting and cleaned by alcohol ultrasonic cleaning.

[0056] S5: Atmospheric plasma spraying was performed with a current of 460A, a power of 25kw, a main gas flow rate of argon gas of 45L / min, a linear speed of 500mm / s, and a spraying distance of 100mm to obtain a Ti-Al-TiC / Cu composite coating.

[0057] Comparative Example 6

[0058] S1: Ti powder, Al powder, TiC powder and polyvinyl alcohol are added into deionized water and stirred to prepare Ti-Al-TiC powder granulation slurry. The molar ratio of Ti powder, Al powder and TiC powder is 1:1:1, and the particle size of Ti powder is 2-15 μm, the particle size of Al powder is 1-5 μm, and the particle size of TiC powder is 3-10 μm.

[0059] S2: The Ti—Al—TiC powder granulation slurry obtained in step S1 is prepared into Ti—Al—TiC spherical powder by spray granulation.

[0060] S3: Mechanically mix the Ti-Al-TiC powder obtained in S2 with Cu powder, wherein the Ti-Al-TiC composite powder accounts for 40% of the total molar ratio, and the Cu powder is a 30-60 μm spherical powder, to obtain a Ti-Al-TiC / Cu composite powder.

[0061] S4: The sprayed surface of the Cu substrate is roughened by sandblasting and cleaned by alcohol ultrasonic cleaning.

[0062] S5: Atmospheric plasma spraying was performed with a current of 460A, a power of 35kw, a main gas flow rate of argon gas of 45L / min, a linear speed of 500mm / s, and a spraying distance of 100mm to obtain a Ti-Al-TiC / Cu composite coating.

[0063] Example coating morphology Figure 1 As shown, the hardness test results of Example 3 and Comparative Example 3 are as follows Figure 2 As shown, due to the low hardness of copper itself, when the Ti-Al-TiC powder content is reduced to 20% and the Cu content is 80%, the hardness is greatly reduced, affecting the comprehensive performance of the coating. Figure 3 As shown in FIG. 5 , when the Ti-Al-TiC powder content increases to 60%, the electrical conductivity decreases, affecting the anti-current friction and wear performance of the coating. Figure 4 As shown in FIG. 1 , when the spraying power is 25 kW, the powder melting effect is poor, the porosity is high, and the coating quality is poor. The hardness test results of Example 6 and Comparative Example 6 are shown in FIG. Figure 5As shown in FIG. 1 , when the spraying power is 35 kW, the coating is oxidized more seriously, resulting in a decrease in the hardness of the coating and poor coating quality. Figure 6 As shown in FIG. 1 , compared with the copper alloy without coating, the coating has a significantly improved anti-current friction and wear performance. Figure 7 As shown, the wear of Comparative Example 2 is more serious, indicating that the selection of powder particle size is important for obtaining a spray coating with excellent performance.

[0064] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalents may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a Ti-Al-TiC / Cu composite coating for improving the current-carrying friction and wear performance of copper alloys, characterized in that: The following steps are involved: S1, adding Ti powder, Al powder, TiC powder and polyvinyl alcohol into deionized water and stirring to prepare Ti-Al-TiC powder granulation slurry; S2, preparing Ti-Al-TiC spherical powder by spray granulation of the Ti-Al-TiC powder obtained in step S1 into granulated slurry; S3, mechanically mixing the Ti-Al-TiC spherical powder obtained in step S2 with Cu powder to obtain Ti-Al-TiC / Cu composite powder; S4, sandblasting roughening and alcohol ultrasonic cleaning of the sprayed surface of the Cu substrate; S5, using the Ti-Al-TiC / Cu composite powder obtained in step S3 to perform atmospheric plasma spraying on the Cu substrate to obtain a Ti-Al-TiC / Cu composite thick coating of 200 to 300 μm.

2. The method for preparing a Ti-Al-TiC / Cu composite coating for improving the current-carrying friction and wear performance of copper alloy according to claim 1, characterized in that: In the step S1, the molar ratio of Ti powder, Al powder and TiC powder is 1:1:1, and the particle size of Ti powder is 2-15 μm, the particle size of Al powder is 1-5 μm, and the particle size of TiC powder is 3-10 μm.

3. The method for preparing a Ti-Al-TiC / Cu composite coating for improving the current-carrying friction and wear performance of copper alloy according to claim 1, characterized in that: In the step S1, the mass of deionized water is 1.5 times the mass of the powder, and the mass of polyvinyl alcohol is 2.5% of the mass of the powder.

4. The method for preparing a Ti-Al-TiC / Cu composite coating for improving the current-carrying friction and wear performance of copper alloy according to claim 1, characterized in that: In the step S3, the Ti-Al-TiC composite powder accounts for 30-50% of the total molar ratio, and the Cu powder is a spherical powder of 30-60 μm.

5. The method for preparing a Ti-Al-TiC / Cu composite coating for improving the current-carrying friction and wear performance of copper alloy according to claim 1, characterized in that: In step S5, the spraying parameters are as follows: current is 450-500A, power is 30-33kw, main gas flow rate of argon is 30-45L / min, line speed is 450-550mm / s; spraying distance is 90-110mm.

6. A Ti-Al-TiC / Cu composite coating for improving the current-carrying friction and wear properties of copper alloy, prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Cited By

  • Electromagnetic track surface coating detection system and wear failure test analysis method

    CN121049340A